Developing Microelectromechanical Systems (MEMS) - Sagoo, Jeevan (Cranfield University, 2008)
Intellectually and technologically, the art of design is one of the oldest forms of mankind’s expression of creativity. Since the early days of primitive man to now, humans have discovered needs that require functional artefacts to perform necessary operations. There are vast differences in the appearance and applications of such artefacts which have varied with time. Developing artefacts to fulfil the new and changing requirements presents a creative response to problem solving at the macro and micro scales. Developments in technology have progressed rapidly driven by the requirement to create smaller artefacts that possess a larger variety of functions. The current developments of micro and nano scale devices have the potential of triggering a technological revolution in many fields. The healthcare industry is utilising micro and nanotechnology applications and aiming these to provide quicker and more affordable medical diagnostic equipment such as the lab on a chip. This is currently being developed to provide a point of care testing to analyse blood samples for different viruses, in a miniature blood testing laboratory which is in the space of a microchip, and providing the appropriate response in a real time environment. Some of these devices are still in the conceptual phases with the possibility for future large volume manufacturing however; the development of microelectromechanical systems or MEMS as they are more commonly known, is performed by the experts with an intuitive based approach. In such context, this thesis proposes a theoretical model for the development of MEMS devices by examination of literature in; generic product development processes used in the engineering and manufacturing areas and capturing how MEMS are currently developed. Parallel to this, development practices currently deployed for MEMS as performed by the experts and practitioners have been illustrated in the form of an As-Is model validated by MEMS experts. The use of IDEF0 to model the existing MEMS development process has provided the necessary tool to analyse the existing process, recognise the limitations, identify the areas of improvement and implement these into a To-Be model proposed for future MEMS development validated by domain experts.